A Meta-Analysis of Extended Reality (XR) Confirms Substantial Efficacy in Enhancing Educational Outcomes and Motivation - Hazem Abdalgader Amer Salem; Rabee Hamza Gareeb (المجلة الأفروآسيوية للبحث العلمي, 2025)
Extended Reality (XR), an umbrella term encompassing immersive technologies such as Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR), is instigating a profound transformation within educational methodologies and environments. This meta-review provides a comprehensive synthesis of empirical evidence derived from 85 high-impact studies, critically examining the efficacy of XR technologies in enhancing learning outcomes and user engagement across a multitude of disciplinary contexts and educational levels. The aggregate analysis demonstrates that XR-based interventions yield statistically significant, substantial improvements in key metrics of educational effectiveness when compared to traditional instructional approaches. Specifically, the findings indicate strong positive effect sizes for both knowledge retention (Hedges’ g = 0.78, p < .001) and procedural skill acquisition (Hedges’ g = 0.82, p < .001). Furthermore, engagement metrics revealed a 43% increase in reported intrinsic motivation among learners and a 2.1-fold extension in task persistence within XR environments. However, a notable high degree of heterogeneity was observed across study results (I² = 87%), suggesting that outcomes are highly contingent on contextual moderating variables. Critical factors identified include the technological maturity and fidelity of the XR application, the degree of its alignment with sound pedagogical principles, and the prior familiarity and experience of the learners. The review also identifies significant impediments to widespread adoption, including persistent issues of technological accessibility and equity (noted in 68% of studies), the potential for cognitive overload (52%), and a pronounced deficit in comprehensive educator training and support (75%). In response to these findings, this paper proposes a structured conceptual framework to guide the effective integration of XR, emphasizing pedagogical grounding and sustainable implementation. Finally, it delineates promising trajectories for future research, particularly in the domains of adaptive XR systems powered by artificial intelligence and the development of collaborative immersive learning spaces.